2014
DOI: 10.1002/aur.1360
|View full text |Cite
|
Sign up to set email alerts
|

Two to Ten Years: Developmental Trajectories of Joint Attention in Children With ASD Who Received Targeted Social Communication Interventions

Abstract: Lay Abstract This study follows 40 children who were participants in a randomized controlled early intervention trial (Kasari et al., 2006, 2008, 2012) from early childhood (2–5 years of age) to elementary school age (8–10 years). The growth trajectories of social-communication and language outcomes in these children were estimated based on 5 time points during that period. The children were grouped by diagnosis at the last follow-up (Autism, ASD, No Diagnosis) and by their original treatment group assignment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 23 publications
4
92
0
Order By: Relevance
“…Treatment effects included more frequent IJA in children aged 21–60 months with teachers and joint engagement with parents (Kaale et al, 2012). The importance of targeting joint attention in EI is highlighted by Gulsrud, Hellemann, Freeman, and Kasari’s (2014) 6-year follow-up of a sub-sample of preschoolers who had received EIBI only or EIBI supplemented with a brief intervention targeting either joint-attention or play (Kasari et al, 2006). The most rapid growth in frequency of triadic gaze and showing behaviour, and most significant expressive language gains, were observed in children who had received the intervention targeting joint attention.…”
Section: Naturalistic Developmental Behavioural Intervention (Ndbi) Amentioning
confidence: 99%
“…Treatment effects included more frequent IJA in children aged 21–60 months with teachers and joint engagement with parents (Kaale et al, 2012). The importance of targeting joint attention in EI is highlighted by Gulsrud, Hellemann, Freeman, and Kasari’s (2014) 6-year follow-up of a sub-sample of preschoolers who had received EIBI only or EIBI supplemented with a brief intervention targeting either joint-attention or play (Kasari et al, 2006). The most rapid growth in frequency of triadic gaze and showing behaviour, and most significant expressive language gains, were observed in children who had received the intervention targeting joint attention.…”
Section: Naturalistic Developmental Behavioural Intervention (Ndbi) Amentioning
confidence: 99%
“…Technological interventions targeting more low-level skills, such as attentional gaze [77], have shown some suggestive results. A recent study [70] investigating the effect of training joint attention skills also yielded promising results. These data suggest that in children with ASC, early pointing could have a causal effect on expressive language development, and illustrate the importance of therapeutic interventions targeting specific gestural and attentional skills early in development.…”
Section: Pilot Results and Discussionmentioning
confidence: 97%
“…Easy-to-use tablet-based technologies have advantage for users with motor impairments, and can also allow interventions targeted at younger children. Early interventions heighten impact on intelligence and communicative skills in later life [70]. However, few technology-based teaching methods have yet managed to generalise 'in-game' skills to real-life situations.…”
Section: Pilot Results and Discussionmentioning
confidence: 99%
“…Gillespie-Lynch and colleagues also suggested examining the relationship with responsiveness to joint attention and early executive functioning in childhood on later outcomes given that executive functioning is related to adaptive functioning in children with autism (Gilotty et al 2012). Gulsrud et al (2014) examined the developmental trajectories of specific joint attention gestures (i.e., pointing, showing, coordinated joint looking) and expressive language over a 6-year period and found that coordinated joint looking and showing increased over time and pointing to share interest increased over the preschool years (3-5 years of age) and then decreased. They also reported a causal relationship between early pointing and later language development; that is, those children with high rates of pointing in the preschool years had better expressive language skills later.…”
Section: Predictors Of Adult Independencementioning
confidence: 99%
“…Participation in the joint attention treatment placed these children on a different developmental trajectory. This highlights that "what" you target and "when" you intervene are important (Gulsrud et al 2014). …”
Section: Predictors Of Adult Independencementioning
confidence: 99%